Productivity and structural heterogeneity in the Brazilian manufacturing sector: Trends and determinants - Eva Yamila Catela; Mario Cimoli; Gabriel Porcile (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
This paper discusses the evolution of firms' productivity and structural heterogeneity (SH) in the Brazilian manufacturing industry in the 2000s. SH is defined (following the Latin American structuralist tradition) as a situation in which a large share of total firms is in the lowest productivity groups of the production structure, and there are very large differences in labour productivity between groups and firms. The paper combines and makes compatible several databases on manufacturing production, innovation and microsocial data for Brazil, in order to measure productivity and SH, to analyze its evolution between 2000 and 2008, and to discuss its determinants. Econometric analyses (k-means cluster methodology to identify productivity groups, and ordered probit models to analyse the determinants of SH) show that increasing returns in innovation and learning prevailed in the 2000s, while policies failed to encourage the catching up process by laggard firms. As a result, SH did not fall in the Brazilian manufacturing sector.
Keywords: L22; L25; O33; O31; 330; structural heterogeneity; technological change; productivity growth; technological asymmetries